(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2023)
In species where males compete for mates, they are expected to develop behaviors and/or morphological adaptations that serve to increase their probability of success. In the harvestman Pachyloides thorellii Holmberg 1878, male-male confrontations have been observed, however, the males do not present any conspicuous feature of sexual dimorphism that could indicate such adaptation to the fight. In this article, we describe agonistic encounters between males of this small, solitary Gonyleptidae and assess whether relative body size influences the duration and outcome of the fight. Confrontations began with quick strikes from legs II and could escalate until using the tubercles and spines of legs IV, one or both legs became hooked. We found no relationship between the body size of the opponents and the duration or outcome of the fight. Our observations suggest that agonistic encounters in P. thorellii are ritualized and escalate through different levels of aggressiveness.